2017
DOI: 10.1016/s0140-6736(17)31327-2
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for management of inflammatory bowel disease (myIBDcoach): a pragmatic, multicentre, randomised controlled trial

Abstract: Maastricht University Medical Centre and Ferring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
291
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(321 citation statements)
references
References 34 publications
10
291
2
3
Order By: Relevance
“…The attrition rate was lower than prior studies with 94% of patients in the telemedicine group completing 1-year follow-up; however, only 75% returned questionnaires at study end 4. Information was not provided on ease of use of the system or patient satisfaction; however, these factors were previously reported as well as accepted 5.…”
Section: Commentarymentioning
confidence: 94%
See 1 more Smart Citation
“…The attrition rate was lower than prior studies with 94% of patients in the telemedicine group completing 1-year follow-up; however, only 75% returned questionnaires at study end 4. Information was not provided on ease of use of the system or patient satisfaction; however, these factors were previously reported as well as accepted 5.…”
Section: Commentarymentioning
confidence: 94%
“…Additionally, maintaining a therapeutic relationship between the patient and treatment team is essential. As this study only assessed 1-year outcomes,4 additional data are needed on maintaining patient engagement and adherence with a telemedicine programme in patients with IBD beyond 1 year.…”
Section: Commentarymentioning
confidence: 99%
“…Remote monitoring can provide clinicians with patient data quickly, allowing faster diagnosis and, if needed, treatment escalation, improving treatment outcomes for individual patients. Remote monitoring in inflammatory bowel disease increased patient empowerment through frequent clinician-patient communication and access to education materials (e.g., e-learning modules) [21,22]. Increased health information provided to clinicians through the telemedicine system allowed for more accurate disease state monitoring, thereby resulting in fewer hospitalizations [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Remote monitoring in inflammatory bowel disease increased patient empowerment through frequent clinician-patient communication and access to education materials (e.g., e-learning modules) [21,22]. Increased health information provided to clinicians through the telemedicine system allowed for more accurate disease state monitoring, thereby resulting in fewer hospitalizations [21,22]. Research has shown associations between patient symptoms (e.g., stool frequency and rectal bleeding) and clinically assessed improvement; patient self-monitoring of symptoms, potentially facilitated by remote monitoring technology, on a weekly/daily basis may be an appropriate avenue to assess treatment benefit in clinical trials [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation